Folk healing and its implications for education - Ponteras, Moises R. (Education quarterly.)
Folk healing as an institution is an organized body of health beliefs and practices in within the context of the culture of the people. Folk healing can contribute to the resolution of the health problems in the rural areas. Legitimizing folk healing is recognizing it as a cultural heritage which has been ingrained in Philippine culture.